Heritage culture and business, Kyoto style craftmanship in the creative economy = Kyōtogata bijinesu : dokusō to keizoku no keieijutsu - Yūzō, Murayama 1953- (Japan Publishing Industry Foundation for Culture, 2019)
"Kyoto, where world-class high-tech industries exist alongside heritage industries. Achieving highly competitive strength by keeping a step ahead of the global standard while maintaining the spirit of harmony that distinguishes Japanese style management. What is the essence of this style of management? How has Kyoto's living traditional culture as a part of daily life been preserved? A thorough study of various unique approaches, based on interviews with managers and craftspeople, Murayama's work covers everything from distinct management styles aimed at increasing workforce motivation to the development of capabilities that yield products with high cultural value, and innovation for the sake of business continuity. This book is packed with valuable hints for the future management of not only Japanese firms but also businesses worldwide"--Provided by publisher.